Analysis of Product Quality, Price Suitability, Product Variation, and Brand Image on Purchase Satisfaction at the ASIKIE BAKERY Bread Factory, Ngronggot District, Nganjuk Regency. - Tahammy, Nikken putri octapia; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to measure or analyze whether there is an influence of product quality, price suitability, product variety and Brand Image simultaneously and partially on purchase satisfaction at the ASIKIE BAKERY bread Design/Method/Approach : This research uses a quantitative approach and uses nonprobability sampling techniques. The population in this study are all buyers who have tasted bread from ASIKIE BAKERY and the sample used in this study is 100 respondents who have made purchases at the ASIKIE BAKERY bread factory which will be analyzed using the classic assumption test method, multiple linear regression method , coefficient of determination and test. hypothesis with a tool called SPSSv23. By using this application you will be able to calculate the data in this research. Research Findings : The results of this research are that product quality and brand image partially influence purchasing satisfaction at the ASIKIE BAKERY bakery , while price suitability and product variety do not partially influence purchasing satisfaction. However, simultaneously the variables of product quality, price suitability, product variety and brand image have a positive and significant effect on purchase satisfaction. Theoretical contribution/Originality: Product quality can increase sales of ASIKIE BAKERY bread in terms of marketing such as brand image seen from the attractive side or not in the bread packaging. Meanwhile, price suitability can be seen in the type of bread, usually standard prices and delicious and attractive bread sell better than bread that is expensive but the product is not good. More product variations are made so that buyers don't get bored with just the same form of bread. Practitionel/Policy implications : This research provides practical implications for the ASIKIE BAKERY bakery . Research limitations: This research only discusses product quality, price suitability, product variety and brand image as independent variables, while purchase satisfaction is the dependent variable.